Estudo fitoquímico de espécies dos gêneros Heliotropium e Euploca (Boraginaceae): busca de moléculas com atividade biológica - Santos, George Luís Dias dos (2022)
Research focused on the phytochemical and pharmacological knowledge of plant species has been increasing in order to contribute, together with ethnopharmacology and folk medicine, to the understanding of the biological responses promoted by these plants. The Boraginaceae family, due to its richness of species and great taxonomic complexity, studies on chemical composition are still scarce. However, research has revealed the presence of secondary metabolites of different classes such as terpenoids, naphthoquinones, flavonoids, phenylpropanoids, alkaloids and lignans. Heliotropium angiospermum, known as "cat's tail", is popularly used in inflammation, wound healing, dysentery and diarrhea. Euploca procumbens, has several popular names and in an ethnomedicinal study it was considered toxic because it has pyrrolizidine alkaloids in its constitution. This work aimed to contribute to the expansion of chemical knowledge by isolating, identifying and/or characterizing new secondary metabolites and evaluating the biological activity of constituents of species of the Boraginaceae family: H. angiospermum and E. procumbens. The plants of both species were collected in the municipality of Campina Grande, state of Paraíba. Each exsiccate was deposited in the Herbarium Arruda Câmara (HACAM) on Campus I of the State University of Paraíba. The plant material, after drying at a temperature of 40 °C for 96 hours, and crushed in a knife mill, was subjected to macerations with 96% ethanol with an interval of 72 h, this process being repeated five times, obtaining the extracts ethanol from the aerial parts and roots of the two species under study. An aliquot of each ethanolic extract was subjected to successive partitions with hexane, chloroform, ethyl acetate and n-butanol and concentrated on a rotary evaporator, obtaining the respective phases. Subsequently, they were submitted to a Sephadex LH-20 chromatographic column and eluted with methanol (100%) to obtain the fractions. An aliquot of Fr3 aerial parts (acetate phase) and Fr3 roots (acetate phase) of H. angiospermum and, Fr5 aerial parts (acetate phase), Fr5 roots (acetate phase) and Fr5 roots (n-butanol phase) of E. procumbens were submitted to the development of an analytical chromatographic method and later transferred to a preparative scale resulting in the isolation of ten compounds, a sucrose diester lignan of the aryldihydronaphthalene type (1), trigonotin A (2), rosmarinic acid (3), narcissine (4) and ethyl lithospermate (5) from the species H. angiospermum and an euploic acid (6), lithospermic acid B (7), lithospermic acid (8), 9´´-methyl lithospermate (9) and luteolin-7-O-glycoside (10) of E. procumbens. Composites 1 and 6 did not induce cytotoxic effects in J774 macrophages, and from the levels of nitric oxide and pro-inflammatory cytokines IL-1β produced by stimulated macrophages, 1 and 6 inhibited the production and/or release of these mediators, with efficacy like that of dexamethasone, considered the anti-inflammatory gold standard. Therefore, these results evidence the anti-inflammatory potential of 1 and 6.